Left ventricular chamber size predicts the race time of Japanese participants in a 100 km ultramarathon - Nagashima, J.; Musha, H.; Takada, H.; Murayama, M. (British Journal of Sports Medicine, 2006)
Objective: As a subanalysis of an echocardiographic study performed on 291 Japanese participants in a 100 km ultramarathon, to estimate predictors of race time. Methods: A total of 247 male participants in a 100 km ultramarathon (age 20-73 years) were examined by echocardiography. Correlations between age, body surface area, monthly running distance, or echocardiographic variables and the race time were examined.